Core competencies for pharmaceutical physicians and drug development scientists - Silva, Honorio; Stonier, Peter; Buhler, Fritz R.; Deslypere, Jean-Paul; Criscuolo, Domenico; Nell, Gerfried; Massud, Joao; Geary, Stewart; Schenk, Johanna; Kerpel-Fronius, Sandor; Koski, Greg; Clemens, Norbert; et al. (Frontiers in Pharmacology, 2013)
Professional groups, such as IFAPP (International Federation of Pharmaceutical Physicians and Pharmaceutical Medicine), are expected to produce the defined core competencies to orient the discipline and the academic programs for the development of future competent professionals and to advance the profession. On the other hand, PharmaTrain, an Innovative Medicines Initiative project, has become the largest public-private partnership in biomedicine in the European Continent and aims to provide postgraduate courses that are designed to meet the needs of professionals working in medicines development. A working group was formed within IFAPP including representatives from PharmaTrain, academic institutions and national member associations, with special interest and experience on Quality Improvement through education. The objectives were: to define a set of core competencies for pharmaceutical physicians and drug development scientists, to be summarized in a Statement of Competence and to benchmark and align these identified core competencies with the Learning Outcomes of the PharmaTrain Base Course. The objectives were successfully achieved. Seven domains and 60 core competencies were identified and aligned accordingly. The effective implementation of training programs using the competencies or the PharmaTrain Learning Outcomes anywhere in the world may transform the drug development process to an efficient and integrated process for better and safer medicines. The PharmaTrain Base Course might provide the cognitive framework to achieve the desired Statement of Competence for Pharmaceutical Physicians and Drug Development Scientists worldwide.